Epitaphs to Empire: On Abe Kōbō and the (Un)Making of the Repatriation Narrative - Christina Yi (Japanese Language and Literature, 2023)
This article considers some of the dynamics of movement and non-movement in the context of East Asia through an examination of the repatriation narrative. By “repatriation narrative,” I refer to a postwar Japanese form of testimonial interlocution which features a first-person returnee narrator/author who explicitly or implicitly addresses a national audience that does not share the experience of repatriation; and which temporalizes repatriation as a memory reconstructed in the present, marked on one end by the end of the war and on the other by the returnee’s “homecoming” to Japan. This article considers the discursive limits of the repatriation narrative by reading Abe Kōbō’s 1948 debut work Owarishi michi no shirube ni (The Signpost at the End of the Road) and 1957 novella Kemonotachi wa kokyō o mezasu (The Beasts Head for Home) in relation to Fujiwara Tei’s 1949 paradigmatic repatriation narrative Nagareru hoshi wa nagarete iru (The Shooting Stars are Alive), focusing in particular on the various literary and geopolitical displacements in all three texts. In reading Abe's works against the larger discursive history of the repatriation narrative, I aim to show how both texts evince a preoccupation with narrative form that is itself a critique.